Peran Kemaafan Pasangan dalam Menjaga Stabilitas Hubungan Romantis pada awal pernikahan - Nurjanis (Indra institute Research & Publication, 2025)
The early years of marriage are a critical period in establishing the foundation of a long-term relationship. One important factor in maintaining stability in romantic relationships is forgiveness between partners. This study aims to explore the role of forgiveness in reducing conflict, strengthening emotional bonds, and promoting harmony in early marital life. Using a qualitative approach with in-depth interviews of newlywed couples, findings indicate that forgiveness serves as an adaptive coping strategy to prevent prolonged conflict, reduce negative emotions, and increase marital satisfaction. Implications suggest that forgiveness is not merely the absence of resentment but a conscious effort to restore trust and intimacy within the relationship.